Home‐grown food and the benefits of sharing: The "intergenerational pact" in postsocialist Moldova. (20th December 2019) - Piras, Simone
Abstract: The policy literature on postsocialist Europe tends to frame smallholders' practices of food self‐provisioning and sharing as driven by necessity and proposes land consolidation to increase productivity and efficiency. However, these practices generate nonfinancial benefits, which need to be accounted for. In this paper, I test the socio‐economic relevance of these practices in the Republic of Moldova, the country with the highest density of farming households in Europe and whose government has embraced the rural modernization agenda to integrate into the EU economic space. I carry out quantitative estimates using the household budget survey and complement the results with qualitative insights from an original smallholder survey. I find that food self‐provisioning and sharing are positively related to subjective well‐being and that there is an "intergenerational pact, " with home‐grown food flowing from late‐adulthood smallholders to urban‐based young families and the vulnerable elderly. A counterfactual analysis shows that poverty and inequality would be higher in the absence of donated food, especially in urban areas. The preservation of smallholder farming through widespread access to land could thus help fight poverty and provide social benefits vis‐à‐vis land consolidation.